First-principles calculations of electronic, optical and transport properties of the inorganic metal halide perovskite CsBI2Br (B = Sn, Ge, Pb) compounds. (May 2021) - Hamideddine, I.; Tahiri, N.; El Bounagui, O.; Ez-Zahraouy, H.
Abstract: Inorganic metal halide perovskite has recently attracted great attention in the past few years. It's has shown great promise as evidenced by its semiconductor behaviors and direct band gap. In this paper, the electronic band structure, optical and transport properties of inorganic metal halide cubic perovskite CsBI2 Br (B= Sn, Ge, Pb) have been investigated using the density functional theory (DFT). The results show that the compounds have a high absorption coefficient (over 10 5 cm -1 ) in visible range. Moreover, a considerable effect on the band-gap was found when we replaced the Lead on CsPbI2 Br with Germanium or Tin; it goes from 1.85 eV for CsPbI2 Br to 1.18 for CsGeI2 Br and 1.07 eV for CsSnI2 Br which are tunable band-gap for optoelectronics applications. However, in this study, it is clearly shown that CsGeI2 Br is a good candidate for photovoltaics applications.